2019
DOI: 10.1007/s11104-019-04308-2
|View full text |Cite
|
Sign up to set email alerts
|

Significance of root hairs at the field scale – modelling root water and phosphorus uptake under different field conditions

Abstract: Background and aims Root hairs play a significant role in phosphorus (P) extraction at the pore scale. However, their importance at the field scale remains poorly understood. Methods This study uses a continuum model to explore the impact of root hairs on the large-scale uptake of P, comparing root hair influence under different agricultural scenarios. High vs low and constant vs decaying P concentrations down the soil profile are considered, along with early vs late precipitation scenarios. Results Simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 71 publications
0
25
1
Order By: Relevance
“…Plant phosphate use efficiency (PUE) is generally correlated with P acquisition efficiency and with root length and architectural traits (Ruiz et al, 2019). Root hairs can increase the effective surface area of plant roots and help the roots to exploit non-accessible stocks of P through accessing the finer pores than the main root axis can enter, thus length and density of root hairs play important role in nutrient acquisition (Ma et al, 2001).…”
Section: Pgpr In Water and Nutrient Acquisitionmentioning
confidence: 99%
“…Plant phosphate use efficiency (PUE) is generally correlated with P acquisition efficiency and with root length and architectural traits (Ruiz et al, 2019). Root hairs can increase the effective surface area of plant roots and help the roots to exploit non-accessible stocks of P through accessing the finer pores than the main root axis can enter, thus length and density of root hairs play important role in nutrient acquisition (Ma et al, 2001).…”
Section: Pgpr In Water and Nutrient Acquisitionmentioning
confidence: 99%
“…The obstruction of this mass flow will disrupt the absorption of nutrients which can have a direct effect on root development, from soil to plants. According to [13] the absorption of P nutrients is influenced by the ability of plant roots and plants as a whole, because in some plants the root hair of plants plays an active role in the absorption of P.…”
Section: Soil Phosphorus Availability and P-uptakesmentioning
confidence: 99%
“…It has been suggested that a better understanding of agricultural ARZ dynamics can inform plant breeding and land management practices in order to take advantage of naturally occurring processes to reduce N runoff (Bodner et al., 2015; Lynch & Whipps, 1990; Sugiyama et al., 2014). Several models have demonstrated the potential for improved nutrient uptake in agricultural vegetation given improved understanding of root exudation (Ruiz et al., 2020; Wang et al., 2013). At an even larger scale, the role of root contribution to soil nutrient cycling has been recognized as an essential piece of our understanding of subsurface C cycling (Gougherty et al., 2018) and, therefore, global C budgets.…”
Section: Introductionmentioning
confidence: 99%